2018
DOI: 10.3390/en11051192
|View full text |Cite
|
Sign up to set email alerts
|

Study on Heat Utilization in an Attached Sunspace in a House with a Central Heating, Ventilation, and Air Conditioning System

Abstract: Based on numerical simulations, the heating load reduction effect of an attached sunspace in winter was determined, and the effective heat utilization method and sunspace design were explored. In this paper, we studied the heating load reduction effect using heat from the sunspace and temperature fluctuation of each room at the time of heat use from the sunspace (sending air from the sunspace to the heating, ventilation, and air conditioning (HVAC) machine room and taking the air to the adjacent rooms). In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Nevertheless, in such facilities, a significant temperature increase in the greenhouse was also observed by Rempel et al [ 11 ]. During research conducted in Japan by Ma et al, temperatures of up to 40 °C were recorded on sunny winter days inside the glazed loggia, and the period in which temperature exceeded 30 °C accounted for over 70% of the measurement time from November to February [ 12 , 13 ]. Experimental studies on historic small buildings in Spain also confirmed the effectiveness of greenhouses in passive heating of the air.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, in such facilities, a significant temperature increase in the greenhouse was also observed by Rempel et al [ 11 ]. During research conducted in Japan by Ma et al, temperatures of up to 40 °C were recorded on sunny winter days inside the glazed loggia, and the period in which temperature exceeded 30 °C accounted for over 70% of the measurement time from November to February [ 12 , 13 ]. Experimental studies on historic small buildings in Spain also confirmed the effectiveness of greenhouses in passive heating of the air.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A different approach, also giving good results as to the energy savings, was using the buffer effect of the solar space, without air exchange with the living zone. This strategy allowed higher internal temperatures to be obtained within the sunspace, and some researchers reported this solution to be more effective than an intensive air extraction [ 13 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…But the application effect is not as ideal as expected, because the construction process is not standardized. In fact, the heat exchange between the sunspace and the house mainly exists in the form of convection [20]. The most effective way to promote the convection is to build vents on the inner wall, which can be controlled manually based on the temperature in the sunspace.…”
Section: Introductionmentioning
confidence: 99%